Developing positive attitudes towards work among Grade IV fast learners through reading - Valencia, Virginia Baer 1946- (College of Education, University of the Philippines-Diliman, 1976)
This paper is an attempt to present enrichment activities designed to develop positive attitude towards work through Reading among the Grade IV fast learners using stories from the basic and supplementary readers for Grade IV in the public schools. Twelve sample lessons were prepared with objectives, stories, learning strategies, and evaluation tools as features of every lesson. The Taxonomy of Educational Objectives: Affective Domain served as guide in the formulation of objectives and evaluation tools, while creative teaching strategies were the means utilized in arriving at the goals. In each of the lessons, actual work experiences were incorporated.